Aquaporin‐2 excretion in hospitalized patients with cirrhosis: Relation to development of renal insufficiency and mortality. Issue 5 (27th April 2017) - Busk, Troels M; Møller, Søren; Pedersen, Erling B; Gerbes, Alexander; Krag, Aleksander; Peck‐Radosavljevic, Markus; Frankova, Sona; Coenraad, Minneke J; Bendtsen, Flemming
Abstract: Background and Aim: Urinary aquaporin‐2 (AQP2) is a parameter of water transport in the principal cells in the distal part of the nephron and involved in water retention in cirrhosis and may be a marker of renal function. The aim of the study was to evaluate AQP2 as a predictor of renal insufficiency and death in patients with cirrhosis. Methods: Urine samples from 199 patients (90 patients without organ failure [Group 1], 58 patients with organ failure excluding renal failure [Group 2], and 51 patients with organ failure including renal failure [Group 3]) from the CANONIC study were analyzed for urine AQP2 and urine osmolality. Results: There was no difference in AQP2 between the three groups. Urine osmolality was significantly lower in patients in Group 3 versus Group 1 and Group 2 ( P = 0.0004). No relation was found between AQP2 and glomerular filtration rate or creatinine; however, AQP2 was a significant predictor of the development of renal insufficiency ( P = 0.0485). In a univariate analysis, AQP2 was a significant predictor of 14 and 28‐day survival, but this was not confirmed in multivariate analysis. Conclusions: Aquaporin‐2 was not associated with disease severity or markers of renal function but was a predictor for the development of renal insufficiency and death. Therefore, its future use as marker of renal insufficiency could be promising, but further research is needed before it can be considered a clinical useful tool.